CURRENT ETIOTROPIC DIAGNOSTICS AND RATIONAL ANTIBACTERIAL THERAPY OF INFECTIVE ENDOCARDITIS - V. G. Seyidov; B. G. Andryukov (Рациональная фармакотерапия в кардиологии)
Up to date principles of diagnostics and treatment of infective endocarditis are presented. Advantages of the special highly-sensitive concentrated media over the standard low-sensitive media for etiological verification of the infective agent are discussed.